2012
DOI: 10.1155/2012/810501
|View full text |Cite
|
Sign up to set email alerts
|

Human Biological Monitoring of Diisononyl Phthalate and Diisodecyl Phthalate: A Review

Abstract: High molecular-weight phthalates, such as diisononyl phthalate (DINP), and diisodecyl phthalate (DIDP), are widely used as plasticizers in the manufacturing of polymers and consumer products. Human biological monitoring studies have employed the metabolites of DINP and DIDP as biomarkers to assess human exposure. In this review, we summarize and analyze publicly available scientific data on chemistry, metabolism, and excretion kinetics, of DINP and DIDP, to identify specific and sensitive metabolites. Human bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…That may explain why the level of MINP was not significantly higher. A previous study showed that the level of MINP was lower than the secondary metabolites at all sampling time points (Saravanabhavan and Murray, 2012). However, in hair samples, the level of MINP was significantly different.…”
Section: Single-dose Treatmentmentioning
confidence: 75%
See 2 more Smart Citations
“…That may explain why the level of MINP was not significantly higher. A previous study showed that the level of MINP was lower than the secondary metabolites at all sampling time points (Saravanabhavan and Murray, 2012). However, in hair samples, the level of MINP was significantly different.…”
Section: Single-dose Treatmentmentioning
confidence: 75%
“…More than 18 billion pounds of phthalates are used each year. They are produced worldwide and are found in children's toys, food packaging, and medical devices (Crinnion, 2010;Colacino et al, 2011;Saravanabhavan and Murray, 2012). Phthalates are endocrine disruptors and affect reproductive outcomes, the development of the male reproductive tract (Waterman et al, 1999;Gray et al, 2000;Kavlock et al, 2002), and sexual differentiation in male rats (Gray et al, 2000;Tyl et al, 2004;Foster, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Because of their widespread use and biological e ects in animals, phthalates were included in the list of regulated (priority) pollutants by the US Environmental Protection Agency and the European Union. 5) Phthalates are easily released from plastic products because phthalates are not chemically bond to plastic products.…”
Section: Phthalates and Toxicological Infor-mationmentioning
confidence: 99%
“…In addition, toxicity of PEs is associated with the length and branching of alkyl side-chain [8,9]. Nevertheless, several studies reported that the high molecular weight PEs are more quickly metabolized and excreted than low molecular weight (short chain) PEs and, consequently, high molecular weight PEs have rather low bioaccumulation potential in the human body [10,11]. Yet, the PEs (and in some cases their metabolites) are considered toxic for animals and/or humans, where the most common effects include hepatoxicity, carcinogenicity, endocrine disruption, fertility decrease (reproductive system), low birth weight, and decreased anogenital distance in children [5,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%